2022
DOI: 10.3390/ph15091083
|View full text |Cite
|
Sign up to set email alerts
|

Brain Targeting of Quetiapine Fumarate via Intranasal Delivery of Loaded Lipospheres: Fabrication, In-Vitro Evaluation, Optimization, and In-Vivo Assessment

Abstract: A liposphere system for intranasal delivery of quetiapine fumarate (QTF) was created to assess the potential for enhanced drug delivery. We investigated the effects of particle size, entrapment effectiveness, poly dispersibility index, and pluronic incorporation percentage on these variables. The optimal formula was examined using a TEM, and investigations into DSC, XRD, and FTIR were made. Optimized liposphere formulation in vitro dissolution investigation with a mean diameter of 294.4 ± 18.2 nm revealed abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The supernatant containing the free SIM was filtered, properly diluted, and quantified for SIM concentration using an ultraviolet (UV) spectrophotometer (Shimadzu UV-1800, Kyoto, Japan) at a predetermined λmax (238 nm). The EE% was computed using the following equation: [ 20 , 37 , 38 ] EE% = (TD − FD)/TD × 100 where EE% is the entrapment efficiency percentage, TD is the total amount of drug, and FD is the free amount of drug in the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant containing the free SIM was filtered, properly diluted, and quantified for SIM concentration using an ultraviolet (UV) spectrophotometer (Shimadzu UV-1800, Kyoto, Japan) at a predetermined λmax (238 nm). The EE% was computed using the following equation: [ 20 , 37 , 38 ] EE% = (TD − FD)/TD × 100 where EE% is the entrapment efficiency percentage, TD is the total amount of drug, and FD is the free amount of drug in the supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, oral administration can also cause unwanted side effects, such as sedation and weight gain. Zaki et al found that the liposphere-based formulation was able to effectively target the brain through the intranasal route, thus lipospheres loaded Quetiapine Fumarate showed high drug loading capacity and better stability and were able to improve the brain uptake and the efficacy of the drug (Zaki et al, 2022). The study also showed that this strategy was a promising alternative to traditional oral administration.…”
Section: Intranasal Deliverymentioning
confidence: 99%